2021
DOI: 10.3390/ijms222011128
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Insulin Resistance, Inflammation, Oxidative Stress, Base Excision Repair and Metabolic Syndrome in Nonalcoholic Fatty Liver Disease

Abstract: One of the most common chronic liver disorders, affecting mainly people in Western countries, is nonalcoholic fatty liver disease (NAFLD). Unfortunately, its pathophysiological mechanism is not fully understood, and no dedicated treatment is available. Simple steatosis can lead to nonalcoholic steatohepatitis and even to fibrosis, cancer, and cirrhosis of the liver. NAFLD very often occurs in parallel with type 2 diabetes mellitus and in obese people. Furthermore, it is much more likely to develop in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 257 publications
(301 reference statements)
2
54
0
1
Order By: Relevance
“…Previous study shows that the monocyte count is an independent predictor of plaque formation and progression in atherosclerosis (Johnsen et al, 2005). Study also demonstrated that the M1 type macrophage/M2 type macrophage ratio was increased during the progression of liver disease (Ziolkowska et al, 2021). On the contrary, HDL-c has anti-inflammatory, antioxidant, and antithrombotic effects, which has the ability to counteract macrophages migration and remove cholesterol from these cells (Akboga et al, 2016;Usta et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…Previous study shows that the monocyte count is an independent predictor of plaque formation and progression in atherosclerosis (Johnsen et al, 2005). Study also demonstrated that the M1 type macrophage/M2 type macrophage ratio was increased during the progression of liver disease (Ziolkowska et al, 2021). On the contrary, HDL-c has anti-inflammatory, antioxidant, and antithrombotic effects, which has the ability to counteract macrophages migration and remove cholesterol from these cells (Akboga et al, 2016;Usta et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence of obesity has dramatically increased worldwide in recent decades [ 1 ] and can be linked with many factors, including metabolic, genetic, environmental, and behavioral impacts [ 2 , 3 ]. Obesity significantly enhances the risk of many diseases, including metabolic syndrome, type 2 diabetes [ 4 ], nonalcoholic fatty liver disease [ 5 ], cardiovascular diseases, and certain types of tumors [ 6 ], which are leading causes of death [ 7 ]. Recently, obesity was recognized as an independent risk factor for mortality from severe acute respiratory syndrome coronavirus (SARS-CoV)-2 infections [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they demonstrate increased blood pressure, LDL and TG, while their HDL level is lower. Thus, T2DM patients with NAFLD have more severe dyslipidemia, hyperinsulinemia and hepatic IR than those without fatty livers [ 156 ].…”
Section: Complicationsmentioning
confidence: 99%